Causal relationship between PCOS and related sex hormones with oral inflammatory diseases: a bidirectional Mendelian randomization study - Min, Qiusi; Chen, Yi; Geng, Hongling; Gao, Qian; Zhang, Xueying; Xu, Min (Frontiers in Endocrinology, 2024)
Background:Observational studies have identified a strong association between polycystic ovary syndrome (PCOS) and hormone levels related to oral inflammatory diseases. To better understand the relationship between them, we conducted an analysis using a two-sample Mendelian randomization (MR) approach.Methods:We gathered summary statistical data from previously published genomewide association studies (GWAS) on PCOS and three sex hormones (AMH, Estradiol, LH) along with four oral inflammatory diseases (painful gums, loose teeth, mouth ulcers, and toothache). We selected single nucleotide polymorphisms (SNPs) as instrumental variables and employed four types of MR analysis methods to evaluate causal relationships between exposure and outcome. Finally, the robustness of our results was further validated through sensitivity tests and reverse MR. Results:We observed that PCOS could increase the risk of mouth ulcers (ORIVW= 1.0013，95%CI: 1.0001-1.0025，PIVW = 0.0278), painful gums (ORIVW= 1.0015，95%CI：1.0003-1.0027，PIVW = 0.0163), and loose teeth (ORIVW= 1.0014，95%CI: 1.0001-1.0027，PIVW = 0.0328). Moreover, LH was also found to increase the risk of mouth ulcers (ORIVW= 1.0031，95%CI: 0.0001-1.0062，PIVW = 0.0457). MR-Egger regression, weighted mode, and WE indicated similar results. Additionally, we discovered no causal link between PCOS and toothache (PIVW＞0.05), LH and painful gums, loose teeth, or toothache (PIVW＞0.05), or AMH and Estradiol level with any of the four oral diseases (PIVW ＞0.05). Conclusion:Our research provides new insights and references for exploring the effects of PCOS and related hormones on oral inflammatory lesions. For patients with PCOS, especially those with elevated LH levels, early intervention measures should be taken to prevent the occurrence of oral inflammatory diseases.